Solar cell, preparation method thereof and solar cell module

By using metal silver electrodes composed of loose layer and dense layer in heterojunction solar cells, the problems of high cost and poor conductivity of low-temperature silver paste are solved, and the effect of reducing production costs and improving conductivity is achieved.

CN119894158APending Publication Date: 2025-04-25BYD CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410680055.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When preparing metal electrodes at low temperatures, the low-temperature silver paste is expensive and has high resistivity, resulting in high production costs and poor conductivity, which affects the cost reduction and efficiency of the battery.

Method used

A metal silver electrode consisting of a loose layer and a dense layer is used. The loose layer is prepared from the first silver paste, and the dense layer is prepared from the second silver paste, and is subjected to high-temperature densification by laser sintering to form an electrode hierarchy structure with different porosities.

Benefits of technology

It reduces the preparation cost of metal electrodes, improves the conductivity, and enhances the end reliability and current conduction efficiency of the battery module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894158A_ABST
    Figure CN119894158A_ABST
Patent Text Reader

Abstract

The invention provides a solar cell, a preparation method thereof and a solar cell module, and particularly relates to the technical field of cell manufacturing, the solar cell comprises metal electrodes arranged on two opposite sides of a cell body, and the metal electrodes comprise loose layers and compact layers which are stacked in sequence in the direction away from the thickness of the cell body; the loose layer and the compact layer are made of silver; the resistivity of the loose layer is greater than that of the compact layer; compared with a traditional metal electrode with uniform structural composition and resistivity, the metal electrode provided by the invention has the loose layer and the compact layer with different porosities, so that the resistivity of the metal electrode is reduced in the current conduction direction, and the conductivity of the metal electrode is improved. Moreover, the compact layer can bear higher series welding temperature, the series welding effect of the welding wire and the compact layer is better in the series welding process of the battery assembly, and the reliability of the battery assembly end is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery manufacturing, and in particular to a solar cell and a preparation method thereof, and a solar cell assembly. Background Art

[0002] Heterojunction solar cells are a highly symmetrical cell structure, with n-type silicon wafers as substrates. After cleaning and texturing, intrinsic amorphous silicon layers are deposited on both sides to play a passivation role. Then p-type amorphous silicon (pn junction) and n-type amorphous silicon (back field) are deposited from both sides. A transparent conductive oxide layer (TCO) is deposited on the outside of the doped layer, and finally, a silver electrode is screen-printed on the TCO.

[0003] Silver electrodes play a key role in heterojunction batteries. They are responsible for connecting the external circuit, conducting the current, and forming a loop. However, due to the particularity of heterojunction solar cells, the entire process needs to be carried out at a lower temperature, otherwise the hydrogenated intrinsic amorphous silicon layer will be destroyed. Therefore, the metal electrode is prepared using low-temperature silver paste. Due to the high price and high resistivity of low-temperature silver paste, it is not conducive to reducing the cost and improving the efficiency of heterojunction solar cells. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a solar cell with low preparation cost and excellent conductive performance, as well as a preparation method of the solar cell and a solar cell module. The specific invention contents are as follows:

[0005] In a first aspect, the present invention provides a solar cell, comprising metal electrodes disposed on opposite sides of a cell body, wherein the metal electrodes comprise a loose layer and a dense layer stacked in sequence along a thickness direction away from the cell body;

[0006] The materials constituting the loose layer and the dense layer both include silver; wherein the resistivity of the loose layer is greater than the resistivity of the dense layer.

[0007] Optionally, the resistivity of the dense layer is 30-40% of the resistivity of the loose layer.

[0008] Optionally, the metal electrode further comprises a transition layer, wherein the transition layer is located between the loose layer and the dense layer;

[0009] The transition layer is formed by mutual penetration of materials constituting the loose layer and the dense layer.

[0010] Optionally, the thickness of the loose layer is 6-10 μm;

[0011] The thickness of the dense layer is 3-7 μm;

[0012] The thickness of the transition layer is 1-2 μm.

[0013] Optionally, the loose layer is formed by preparing a first silver paste, and the dense layer is formed by preparing a second silver paste;

[0014] The first silver paste comprises: a first silver powder, an epoxy resin and a first organic component;

[0015] The second silver paste comprises: a second silver powder, a glass powder, a second organic component and an aluminum powder;

[0016] Wherein, the first silver powder is formed by mixing flake silver powder and spherical silver powder;

[0017] The second silver powder is spherical silver powder;

[0018] The first organic component includes at least one of diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy) ethyl acetate, butyl carbitol acetate and lauryl peroxide;

[0019] The second organic component includes at least one of diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy) ethyl acetate, butyl carbitol acetate and alcohol ester dodecahydrate.

[0020] Optionally, in the first silver paste, the mass proportion of the first silver powder is 85-95%, the mass proportion of the epoxy resin is 1-10%, and the mass proportion of the first organic component is 0.6-10%;

[0021] In the second silver paste, the mass proportion of the second silver powder is 90-92%, the mass proportion of the glass powder is 4-6%, the mass proportion of the second organic component is 2-4%, and the mass proportion of the aluminum powder is 0.01-0.05%.

[0022] Optionally, the battery body comprises: an N-type single crystal silicon substrate, an intrinsic hydrogenated amorphous silicon film layer, an n-type amorphous silicon layer and a TCO layer sequentially stacked on a first surface of the N-type single crystal silicon substrate, and an intrinsic hydrogenated amorphous silicon film layer, a p-type amorphous silicon layer and a TCO layer sequentially stacked on a second surface of the N-type single crystal silicon substrate;

[0023] The first surface is opposite to the second surface.

[0024] In a second aspect, the present invention provides a method for preparing a solar cell, the method comprising:

[0025] Depositing a first silver paste on the transparent conductive oxide layer of the battery body;

[0026] Drying the deposited first silver paste to form a loose layer of metal electrode;

[0027] Depositing a second silver paste on the surface of the loose layer;

[0028] Performing high-temperature densification treatment on the deposited second silver paste by laser sintering to form a dense layer of the metal electrode;

[0029] Wherein, the resistivity of the loose layer is greater than the resistivity of the dense layer.

[0030] Optionally, the resistivity of the first silver paste is 4.0*10 -6 ~6.0*10 -6 Ω·cm, the resistivity of the second silver paste is 1.0*10 -6 ~2.0*10 -6 Ω·cm.

[0031] Optionally, under the action of laser, the second silver paste partially penetrates into the surface pores of the loose layer to form a transition layer;

[0032] The deposition thickness of the first silver paste is 5-10 μm; the deposition thickness of the second silver paste is 2-8 μm; and the thickness of the transition layer is 1-2 μm.

[0033] Optionally, the temperature of the drying process is no greater than 200°C;

[0034] The diameter of the laser spot emitted by the laser light source used in the laser sintering is not greater than the width of the deposited second silver paste.

[0035] Optionally, the method for preparing the battery body includes:

[0036] Providing an N-type single crystal silicon substrate;

[0037] Depositing an intrinsic hydrogenated amorphous silicon film layer, a p-type amorphous silicon film layer and a transparent conductive oxide layer in sequence on a first surface of an N-type single crystal silicon substrate;

[0038] Depositing an intrinsic hydrogenated amorphous silicon film layer, an n-type amorphous silicon layer and a transparent conductive oxide layer in sequence on the second surface of the N-type single crystal silicon substrate to obtain the battery body;

[0039] wherein the first surface is opposite to the second surface;

[0040] The target material of the transparent conductive oxide layer includes any one of indium tin oxide, indium oxide doped with tungsten and indium oxide doped with cerium.

[0041] In a third aspect, the present invention provides a solar cell assembly, wherein the solar cell assembly comprises a plurality of solar cells as described in the first aspect.

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] The solar cell provided by the present invention comprises metal electrodes arranged on opposite sides of the battery body, wherein the metal electrodes are sequentially stacked with loose layers and dense layers in a direction away from the thickness of the battery body; the materials constituting the loose layers and the dense layers both comprise silver; the resistivity of the loose layers is greater than the resistivity of the dense layers; compared with the conventional metal electrodes having uniform structural composition and resistivity, the metal electrodes provided by the present invention have loose layers and dense layers with different porosities, which reduces the resistivity of the metal electrodes in the current conduction direction and improves the conductivity of the metal electrodes. In addition, the dense layers can withstand higher series welding temperatures, and in the process of series welding of battery components, the series welding effect of the welding wire and the dense layers is better, and the reliability of the battery component end is improved.

[0044] The present invention also provides a method for preparing a solar cell, the method comprising: depositing a first silver paste on a battery body; drying the deposited first silver paste to form a loose layer of a metal electrode; depositing a second silver paste on the surface of the loose layer; performing a high-temperature densification treatment on the deposited second silver paste by laser sintering to finally obtain the metal electrode; wherein the resistivity of the first silver paste is greater than the resistivity of the second silver paste; compared with the expensive price of traditional silver electrode paste, the present invention uses the first silver paste in combination with the second silver paste to deposit and prepare the metal electrode, which greatly reduces the preparation cost of the metal electrode, improves the conductivity of the metal electrode, and is beneficial to reducing the cost and improving the efficiency of heterojunction solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 A schematic diagram of the structure of a solar cell provided by an embodiment of the present invention is shown;

[0047] Figure 2 SEM images of the surface and cross section of the loose layer of the metal electrode provided by the embodiment of the present invention are shown;

[0048] Figure 3 SEM images of the surface and cross section of the dense layer of the metal electrode provided by the embodiment of the present invention are shown;

[0049] Figure 4 A flow chart of a method for preparing a solar cell provided by an embodiment of the present invention is shown;

[0050] Figure 5A flow chart of a method for preparing a solar cell body provided by an embodiment of the present invention is shown.

[0051] Description of reference numerals:

[0052] 1-N-type single crystal silicon substrate, 2-intrinsic hydrogenated amorphous silicon film layer, 3-n-type amorphous silicon layer, 4-p-type amorphous silicon layer, 5-TCO layer, 6-metal electrode, 6-1-loose layer, 6-2-dense layer. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.

[0054] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.

[0055] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the description of the present invention.

[0056] In the description of the present invention, it should be understood that the use of terms such as "low temperature" and "high temperature" to limit components is only for the convenience of stratifying the corresponding components. If not otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0057] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0058] Due to the particularity of heterojunction solar cells, the entire metal electrode preparation process needs to be carried out at a relatively low temperature. This results in most traditional heterojunction solar cells using low-temperature silver paste to prepare metal electrodes. Low-temperature silver paste is expensive and has a high resistivity, which not only increases the production cost of heterojunction solar cells, but also reduces the conductivity of the metal electrode, which is not conducive to the expansion of the production scale of heterojunction batteries.

[0059] Based on this, the present invention proposes to adjust the slurry composition of the printed metal electrode, adopt a secondary printing method, deposit the first silver paste and the second silver paste on the battery body in sequence, and finally obtain a metal silver electrode composed of a stacked loose layer and a dense layer. The specific implementation method is as follows:

[0060] In a first aspect, the present invention provides a solar cell, comprising metal electrodes 6 disposed on opposite sides of a cell body, Figure 1 The schematic diagram of the structure of the solar cell provided by the embodiment of the present invention is shown as follows: Figure 1 As shown, along the thickness direction away from the battery body, the metal electrode 6 includes a loose layer 6-1 and a dense layer 6-2 stacked in sequence; the size relationship between the loose layer 6-1 and the dense layer 6-2 satisfies that the orthographic projection of the loose layer 6-1 on the battery body can be covered by the orthographic projection of the dense layer 6-2 on the battery body, or the orthographic projection of the loose layer 6-1 on the battery body coincides with the orthographic projection of the dense layer 6-2 on the battery body. Specifically, the thickness of the dense layer 6-2 accounts for 20-80% of the total thickness of the metal electrode.

[0061] In some embodiments, the thickness of the loose layer 6 - 1 may be greater than the thickness of the dense layer 6 - 2 .

[0062] In specific implementation, the solar cell provided by the present invention uses a metal silver electrode as an electrode connected to an external circuit to conduct current and form a loop. Therefore, the constituent materials of the loose layer 6-1 and the dense layer 6-2 constituting the metal silver electrode both include silver, and the constituent materials of the loose layer 6-1 and the dense layer 6-2 are different, so that the resistivity of the loose layer 6-1 is greater than the resistivity of the dense layer 6-2. The resistivity of the dense layer 6-2 is 30%-40% of that of the loose layer 6-1.

[0063] In specific implementation, the loose layer 6-1 is prepared by the first silver paste, and the dense layer 6-2 is prepared by the second silver paste; the present invention uses the first silver paste and the second silver paste in combination, and adopts the method of secondary printing of metal electrodes, and first prints the first silver paste on the battery body. Since the first silver paste directly contacts the battery body, the hydrogenated intrinsic amorphous silicon layer in the battery body is sensitive to high temperature, and high temperature will cause it to degrade and affect the performance of the solar cell. Therefore, the first silver paste must have a lower curing temperature to prevent high temperature from damaging the hydrogenated intrinsic amorphous silicon layer. The composition of the first silver paste used in the embodiment of the present invention includes, by mass percentage: 85-95% of the first silver powder, 1-10% of the epoxy resin, and 0.6-10% of the first organic component; wherein the first silver powder is formed by mixing flaky silver powder and spherical silver powder, and the mass proportion can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%; the first organic component includes diethylene glycol butyl ether acetate, At least one of 2-(2-butoxyethoxy)ethyl acetate, butyl carbitol acetate and alcohol ester twelve may account for 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% by weight; the epoxy resin may account for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% by weight; the resistivity of the first silver paste is 4.0*10 -6 ~6.0*10 -6 Ω·cm, and the curing temperature is 150-200°C, specifically 150°C, 160°C, 170°C, 180°C, 190°C or 200°C. The first silver paste is used for the first printing to prepare the metal silver electrode, and the first silver paste is cured to form a loose layer 6-1, and the thickness of the loose layer 6-1 can be controlled to be 6-10μm, specifically 6μm, 7μm, 8μm, 9μm or 10μm.

[0064] Furthermore, the second silver paste is printed on the surface of the loose layer 6-1. Due to the presence of the loose layer 6-1, the curing process of the second silver paste is not limited by temperature, and the price of the silver paste with a low curing temperature is significantly higher than that of the silver paste with a high curing temperature. Therefore, the composition of the second silver paste used in the embodiment of the present invention includes, by mass percentage, 90-92% of the second silver powder, 4-6% of the glass powder, 2-4% of the second organic component, and 0.01-0.05% of the aluminum powder; wherein the second silver powder is spherical silver powder, and the mass percentage can be 90%, 91% or 92%; the second organic component includes at least one of diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy) ethyl acetate, butyl carbitol acetate and alcohol ester lauryl peroxide, and the mass percentage can be 2%, 3% or 4%; the glass powder is composed of one or more of PbO, TeO2, and Bi2O3, and the mass percentage can be 5%, 5% or 6%. The resistivity of the second silver paste is 1.0*10 -6 ~2.0*10 -6 Ω·cm. A metal silver electrode is prepared by secondary printing using a second silver paste. After the second silver paste is cured, a dense layer 6-2 is formed. The thickness of the dense layer 6-2 is controlled to be 3-7μm, specifically 3μm, 4μm, 5μm, 6μm or 7μm. The metal electrode provided by the present invention is formed by stacking a loose layer 6-1 and a dense layer 6-2. The loose layer 6-1 and the dense layer 6-2 have different porosities, which reduces the resistivity of the metal electrode in the current conduction direction. Compared with traditional metal electrodes with uniform structural composition and resistivity, the conductive performance of the metal electrode provided by the embodiment of the present invention is significantly improved, and the preparation cost is significantly reduced.

[0065] In some embodiments, the metal electrode further includes a transition layer, which is located between the loose layer 6-1 and the dense layer 6-2; the transition layer is formed by the materials constituting the loose layer 6-1 and the dense layer 6-2 interpenetrating under the action of high temperature. The thickness of the transition layer is 1-2 μm. The thickness of the transition layer is less than the thickness of the loose layer 6-1 and also less than the thickness of the dense layer 6-2.

[0066] Figure 2 SEM images of the surface and cross section of the loose layer of the metal electrode provided in the embodiment of the present invention are shown, wherein (a) shows a surface SEM image of the loose layer 6-1, and (b) shows a cross-sectional SEM image of the loose layer 6-1; Figure 3 Surface and cross-sectional SEM images of the dense layer of the metal electrode provided in the embodiment of the present invention are shown, wherein (c) shows a surface SEM image of the dense layer 6-2, and (d) shows a cross-sectional SEM image of the dense layer 6-2; Figure 2 and Figure 3As shown, the loose layer 6-1 and the dense layer 6-2 have different porosities, and the porosity of the loose layer 6-1 is significantly greater than that of the dense layer 6-2.

[0067] In some embodiments, the battery body includes: an N-type single crystal silicon substrate 1, an intrinsic hydrogenated amorphous silicon film layer 2, an n-type amorphous silicon layer 3 and a TCO layer 5 arranged in sequence on the first surface of the N-type single crystal silicon substrate 1, and an intrinsic hydrogenated amorphous silicon film layer 2, a p-type amorphous silicon layer 4 and a TCO layer 5 arranged in sequence on the second surface of the N-type single crystal silicon substrate 1; wherein the first surface is opposite to the second surface.

[0068] In a second aspect, the present invention provides a method for preparing a solar cell. Figure 4 The flowchart of the method for preparing a solar cell provided by an embodiment of the present invention is shown as follows: Figure 4 As shown, the preparation method comprises:

[0069] Step 1: depositing a first silver paste on the TCO layer of the battery body;

[0070] Step 2, drying the deposited first silver paste to form a loose layer of the metal electrode;

[0071] Step 3, depositing a second silver paste on the surface of the loose layer;

[0072] Step 4: Perform high-temperature densification treatment on the deposited second silver paste by laser sintering to form a dense layer of the metal electrode.

[0073] In the embodiment of the present invention, a first silver paste with a low curing temperature is deposited on the battery body. The composition of the first silver paste used is calculated by mass percentage, including: 85-95% of a first silver powder, 1-10% of an epoxy resin, and 0.6-10% of a first organic component; wherein the first silver powder is formed by mixing flaky silver powder and spherical silver powder, and the first organic component includes at least one of diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy) ethyl acetate, butyl carbitol acetate, and alcohol ester lauryl peroxide; the resistivity of the first silver paste is 4.0*10 -6 ~6.0*10 -6 Ω·cm, the curing temperature selected when drying the deposited first silver paste is not greater than 200° C., preferably 150-200° C., specifically 150° C., 160° C., 170° C., 180° C., 190° C. or 200° C. After curing, a loose layer of the metal electrode is formed.

[0074] Furthermore, the second silver paste is printed on the surface of the loose layer. Due to the presence of the loose layer, the curing process of the second silver paste can be carried out at high temperature without being restricted by temperature, and the price of the silver paste with a low curing temperature is significantly higher than that of the silver paste with a high curing temperature. Therefore, the composition of the second silver paste used in the embodiment of the present invention includes, by mass percentage, 90-92% of the second silver powder, 4-6% of the glass powder, 2-4% of the second organic component, and 0.01-0.05% of the aluminum powder; wherein the second silver powder is spherical silver powder, and the mass percentage can be 90%, 91% or 92%; the second organic component includes at least one of diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy) ethyl acetate, butyl carbitol acetate and alcohol ester lauryl peroxide, and the mass percentage can be 2%, 3% or 4%; the glass powder is composed of one or more of PbO, TeO2, and Bi2O3, and the mass percentage can be 5%, 5% or 6%.

[0075] The resistivity of the second silver paste used in the embodiment of the present invention is lower than that of the first silver paste. After the second printing is completed, the second silver paste is solidified by laser sintering. Since high temperature will destroy the integrity of the hydrogenated intrinsic amorphous silicon layer and the TCO layer in the battery body, the diameter of the laser spot emitted by the laser light source used in laser sintering is not greater than the width of the deposited high-temperature silver paste. The high temperature of laser sintering causes part of the resin in the loose layer to pyrolyze, resulting in pores of varying sizes. The spherical silver powder in the second silver paste softens and melts, and penetrates into the pores on the surface of the loose layer under the action of gravity. During the cooling process, silver microcrystals are precipitated and connected to the silver in the loose layer, thereby forming a transition layer between the loose layer and the dense layer. It should be noted that the present invention does not specifically limit the laser light source used for laser sintering, and either an ordinary fiber laser beam or a semiconductor laser beam can be used; the glass powder in the second silver paste is composed of one or more of PbO, TeO2, and Bi2O3, which further enhances the bonding strength of the penetration area, so that the two pastes are well fused in structure. In the formed transition layer, the flaky silver powder accounts for 13% to 16%, the spherical silver powder accounts for 82% to 86%, and the glass phase accounts for 1% to 2%; the presence of the transition layer improves the compactness between the contact surfaces of the two, increases the carrier transmission area, and makes there is no obvious connection interface between the loose layer and the dense layer, thereby better ensuring the conductive performance of the metal electrode.

[0076] Figure 5 The flowchart of the method for preparing the solar cell body provided by the embodiment of the present invention is shown as follows: Figure 5 As shown, the preparation method of the battery body includes:

[0077] Step 11, providing an N-type single crystal silicon substrate;

[0078] Step 12: depositing an intrinsic hydrogenated amorphous silicon film layer, a p-type amorphous silicon film layer and a TCO layer in sequence on the first surface of the N-type single crystal silicon substrate;

[0079] Step 13: depositing an intrinsic hydrogenated amorphous silicon film layer, an n-type amorphous silicon layer and a TCO layer in sequence on the second surface of the N-type single crystal silicon substrate to obtain the battery body.

[0080] In a specific implementation, the first surface is opposite to the second surface, and the target material of the TCO layer includes any one of indium tin oxide, indium oxide doped with tungsten and indium oxide doped with cerium.

[0081] In a third aspect, the present invention provides a solar cell assembly, which includes a plurality of solar cells as described in the first aspect.

[0082] In order to enable those skilled in the art to more clearly understand the present invention, a solar cell and a preparation method thereof according to the present invention are now described in detail through the following embodiments.

[0083] Example 1

[0084] This embodiment provides Figure 1 The manufacturing method of the heterojunction battery shown specifically includes the following steps:

[0085] Providing an N-type single crystal silicon substrate 1;

[0086] The N-type single crystal silicon substrate 1 is cleaned and textured to form a special pyramid texture surface to reduce light reflection and trap light.

[0087] An intrinsic hydrogenated amorphous silicon film is deposited on the back side of the substrate 1 to form an intrinsic layer 2 on the back side; then an intrinsic hydrogenated amorphous silicon film is deposited on the front side to form an intrinsic layer 2 on the front side; then n-type amorphous silicon is deposited on the surface of the front intrinsic layer 2 to form an n-type amorphous silicon layer 3; then p-type amorphous silicon is deposited on the surface of the back intrinsic layer 2 to form a p-type amorphous silicon layer 4; finally, a TCO layer 5 is deposited on the surfaces of the n-type amorphous silicon layer 3 and the p-type amorphous silicon layer 4, respectively, and the target material used to prepare the TCO layer 5 is indium tin oxide (In2O3 / SnO2 mass ratio is 99:1).

[0088] The first silver paste is screen-printed on the surface of the TCO layer 5. The composition of the first silver paste is 85% flaky silver powder, 10% spherical silver powder, 8% epoxy resin, and 2% butyl carbitol acetate in mass percentage. The printing height of the first silver paste is 7 μm. The low-temperature silver paste is dried in a drying furnace to form a loose layer 6-1 of the metal electrode 6. The drying temperature is 200°C.

[0089] A second silver paste is further screen-printed on the surface of the loose layer 6-1. The composition of the second silver paste is 91% spherical silver powder, 5% glass powder, 3.99% diethylene glycol butyl ether acetate and 0.01% aluminum powder by mass percentage. The screen-printing height of the second silver paste is 6μm. The high-temperature silver paste is solidified by laser sintering, and the spot size of the laser emitted by the laser light source irradiating the metal electrode is consistent with the screen-printing width of the second silver paste, which is solidified to form a dense layer 6-2 of the metal electrode 6.

[0090] Example 2

[0091] This embodiment provides Figure 1 The manufacturing method of the heterojunction battery shown specifically includes the following steps:

[0092] Providing an N-type single crystal silicon substrate 1;

[0093] The N-type single crystal silicon substrate 1 is cleaned and textured to form a special pyramid texture surface to reduce light reflection and trap light.

[0094] An intrinsic hydrogenated amorphous silicon film is deposited on the back side of the substrate 1 to form an intrinsic layer 2 on the back side; then an intrinsic hydrogenated amorphous silicon film is deposited on the front side to form an intrinsic layer 2 on the front side; then n-type amorphous silicon is deposited on the surface of the front intrinsic layer 2 to form an n-type amorphous silicon layer 3; then p-type amorphous silicon is deposited on the surface of the back intrinsic layer 2 to form a p-type amorphous silicon layer 4; finally, a TCO layer 5 is deposited on the surfaces of the n-type amorphous silicon layer 3 and the p-type amorphous silicon layer 4, respectively, wherein the target material used to prepare the TCO layer 5 is indium oxide doped tungsten (IWO).

[0095] The first silver paste is screen-printed on the surface of the TCO layer 5. The composition of the first silver paste is 80% flaky silver powder, 15% spherical silver powder, 8% epoxy resin, and 2% butyl carbitol acetate in mass percentage. The printing height of the first silver paste is 6 μm. The low-temperature silver paste is dried in a drying furnace to form a loose layer 6-1 of the metal electrode 6. The drying temperature is 170°C.

[0096] A second silver paste is further screen-printed on the surface of the loose layer 6-1. The composition of the second silver paste is 90% spherical silver powder, 6% glass powder, 3.99% diethylene glycol butyl ether acetate and 0.01% aluminum powder by mass percentage. The screen-printed height of the second silver paste is 7μm. The high-temperature silver paste is solidified by laser sintering, and the spot size of the laser emitted by the laser light source irradiating the metal electrode is consistent with the screen-printed width of the second silver paste, which is solidified to form a dense layer 6-2.

[0097] Example 3

[0098] This embodiment provides Figure 1The manufacturing method of the heterojunction battery shown specifically includes the following steps:

[0099] Providing an N-type single crystal silicon substrate 1;

[0100] The N-type single crystal silicon substrate 1 is cleaned and textured to form a special pyramid texture surface to reduce light reflection and trap light.

[0101] An intrinsic hydrogenated amorphous silicon film is deposited on the back side of the substrate 1 to form an intrinsic layer 2 on the back side; then an intrinsic hydrogenated amorphous silicon film is deposited on the front side to form an intrinsic layer 2 on the front side; then n-type amorphous silicon is deposited on the surface of the front intrinsic layer 2 to form an n-type amorphous silicon layer 3; then p-type amorphous silicon is deposited on the surface of the back intrinsic layer 2 to form a p-type amorphous silicon layer 4; finally, a TCO layer 5 is deposited on the surfaces of the n-type amorphous silicon layer 3 and the p-type amorphous silicon layer 4, respectively, wherein the target material used to prepare the TCO layer 5 is indium oxide doped with cerium (ICO).

[0102] The first silver paste is screen-printed on the surface of the TCO layer 5. The composition of the first silver paste is 75% flaky silver powder, 20% spherical silver powder, 8% epoxy resin, and 2% butyl carbitol acetate in mass percentage. The printing height of the first silver paste is 6 μm. The low-temperature silver paste is dried in a drying furnace to form a loose layer 6-1 of the metal electrode 6. The drying temperature is 150°C.

[0103] A second silver paste is further screen-printed on the surface of the loose layer 6-1. The composition of the second silver paste is 92% spherical silver powder, 4% glass powder, 3.99% 2-(2-butoxyethoxy) ethyl acetate and 0.01% aluminum powder by mass percentage. The screen-printed height of the second silver paste is 7 μm. The high-temperature silver paste is solidified by laser sintering, and the spot size of the laser emitted by the laser light source irradiating the metal electrode is consistent with the screen-printed width of the second silver paste, which is solidified to form a dense layer 6-2 of the metal electrode 6.

[0104] Example 4

[0105] This embodiment provides Figure 1 The manufacturing method of the heterojunction battery shown specifically includes the following steps:

[0106] Providing an N-type single crystal silicon substrate 1;

[0107] The N-type single crystal silicon substrate 1 is cleaned and textured to form a special pyramid texture surface to reduce light reflection and trap light.

[0108] An intrinsic hydrogenated amorphous silicon film is deposited on the back side of the substrate 1 to form an intrinsic layer 2 on the back side; then an intrinsic hydrogenated amorphous silicon film is deposited on the front side to form an intrinsic layer 2 on the front side; then n-type amorphous silicon is deposited on the surface of the front intrinsic layer 2 to form an n-type amorphous silicon layer 3; then p-type amorphous silicon is deposited on the surface of the back intrinsic layer 2 to form a p-type amorphous silicon layer 4; finally, a TCO layer 5 is deposited on the surfaces of the n-type amorphous silicon layer 3 and the p-type amorphous silicon layer 4, respectively, wherein the target material used to prepare the TCO layer 5 is indium tin oxide (In2O3 / SnO2 mass ratio is 99:1).

[0109] The first silver paste is screen-printed on the surface of the TCO layer 5. The composition of the first silver paste is 85% flaky silver powder, 10% spherical silver powder, 5% epoxy resin, and 5% 2-(2-butoxyethoxy) ethyl acetate in mass percentage. The printing height of the first silver paste is 8 μm. The low-temperature silver is dried in a drying furnace to form a loose layer 6-1 of the metal electrode 6. The drying temperature is 150°C.

[0110] A second silver paste is further screen-printed on the surface of the loose layer 6-1. The composition of the second silver paste is 90% spherical silver powder, 6% glass powder, 3.99% 2-(2-butoxyethoxy) ethyl acetate and 0.01% aluminum powder by mass percentage. The screen-printing height of the second silver paste is 5 μm. The high-temperature silver paste is solidified by laser sintering, and the spot size of the laser emitted by the laser light source irradiating the metal electrode is consistent with the screen-printing width of the second silver paste, which is solidified to form a dense layer 6-2 of the metal electrode 6.

[0111] Comparative Example 1

[0112] Compared with Example 1, the difference of the comparative example is that only the first silver paste is used to print the metal electrode, and the printing height is 13 μm.

[0113] Performance Testing

[0114] (1) Current density-voltage characteristic curve (JV) test

[0115] The cells prepared in Examples 1-4 and Comparative Example 1 were placed in an IV tester and tested for electrical properties under standard conditions (light intensity 1000 W / m 2 , AM1.5, temperature 25℃), the battery cell obtains non-equilibrium carriers under the flashing of xenon lamp, the external circuit can obtain the current and voltage information at both ends of the battery cell, and display the IV curve, and the open circuit voltage, short circuit current, fill factor and electrical conversion efficiency information shown in Table 1 are obtained from the IV curve.

[0116] Table 1 shows the test results data obtained by performing relevant performance tests on the solar cells prepared in Examples 1-4 and Comparative Example 1. As shown in Table 1, the solar cells prepared in Examples 1-4 performed better than Comparative Example 1 in the electrical conversion efficiency, short-circuit current and fill factor tests.

[0117] Table 1 Relevant performance data of solar cells prepared in Examples 1-4 and Comparative Example 1

[0118] Electrical conversion efficiency / % Open circuit voltage / V Short circuit current / A Fill factor / % Example 1 25.69 0.752 8.706 86.514 Example 2 25.53 0.751 8.681 86.347 Example 3 25.62 0.752 8.693 86.447 Example 4 25.52 0.751 8.682 86.299 Comparative Example 1 25.36 0.751 8.648 86.136

[0119] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.

[0120] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.

[0121] The solar cell and its preparation method, and the solar cell module provided by the present invention are introduced in detail above. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A solar cell comprising metal electrodes disposed on opposite sides of a cell body, characterized in that: Along the thickness direction away from the battery body, the metal electrode includes a loose layer and a dense layer stacked in sequence; The materials constituting the loose layer and the dense layer both include silver; wherein the resistivity of the loose layer is greater than the resistivity of the dense layer.

2. The solar cell according to claim 1, characterized in that: The resistivity of the dense layer is 30-40% of the resistivity of the loose layer.

3. The solar cell according to claim 1, characterized in that: The metal electrode further comprises a transition layer, wherein the transition layer is located between the loose layer and the dense layer; The transition layer is formed by mutual penetration of materials constituting the loose layer and the dense layer.

4. The solar cell according to claim 3, characterized in that: The thickness of the loose layer is 6-10 μm; The thickness of the dense layer is 3-7 μm; The thickness of the transition layer is 1-2 μm.

5. The solar cell according to any one of claims 1 to 4, characterized in that: The loose layer is formed by preparing a first silver paste, and the dense layer is formed by preparing a second silver paste; The first silver paste comprises: a first silver powder, an epoxy resin and a first organic component; The second silver paste comprises: a second silver powder, a glass powder, a second organic component and an aluminum powder; Wherein, the first silver powder is formed by mixing flaky silver powder and spherical silver powder; The second silver powder is spherical silver powder; The first organic component includes at least one of diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy) ethyl acetate, butyl carbitol acetate and alcohol ester dodecahydrate; The second organic component includes at least one of diethylene glycol butyl ether acetate, 2-(2-butoxyethoxy) ethyl acetate, butyl carbitol acetate and alcohol ester dodecahydrate.

6. The solar cell according to claim 5, characterized in that: In the first silver paste, the mass proportion of the first silver powder is 85-95%, the mass proportion of the epoxy resin is 1-10%, and the mass proportion of the first organic component is 0.6-10%; In the second silver paste, the mass proportion of the second silver powder is 90-92%, the mass proportion of the glass powder is 4-6%, the mass proportion of the second organic component is 2-4%, and the mass proportion of the aluminum powder is 0.01-0.05%.

7. The solar cell according to claim 1, characterized in that: The battery body comprises: an N-type single crystal silicon substrate, an intrinsic hydrogenated amorphous silicon film layer, an n-type amorphous silicon layer and a transparent conductive oxide layer sequentially stacked on a first surface of the N-type single crystal silicon substrate, and an intrinsic hydrogenated amorphous silicon film layer, a p-type amorphous silicon layer and a transparent conductive oxide layer sequentially stacked on a second surface of the N-type single crystal silicon substrate; The first surface is opposite to the second surface.

8. A method for preparing a solar cell, characterized in that: The preparation method comprises: Depositing a first silver paste on the transparent conductive oxide layer of the battery body; Drying the deposited first silver paste to form a loose layer of the metal electrode; Depositing a second silver paste on the surface of the loose layer; The deposited second silver paste is processed by laser sintering to form a dense layer of the metal electrode; Wherein, the resistivity of the first silver paste is greater than the resistivity of the second silver paste.

9. The method for preparing a solar cell according to claim 8, characterized in that: The resistivity of the first silver paste is 4.0*10 -6 ~6.0*10 -6 Ω·cm, the resistivity of the second silver paste is 1.0*10 -6 ~2.0*10 -6 Ω·cm.

10. The method for preparing a solar cell according to claim 8, characterized in that: Under the action of laser, the second silver paste partially penetrates into the surface pores of the loose layer to form a transition layer; The deposition thickness of the first silver paste is 5-10 μm; the deposition thickness of the second silver paste is 2-8 μm; and the thickness of the transition layer is 1-2 μm.

11. The method for preparing a solar cell according to claim 8, characterized in that: The temperature of the drying process is not greater than 200°C; The diameter of the laser spot emitted by the laser light source used in the laser sintering is not greater than the width of the deposited second silver paste.

12. The method for preparing a solar cell according to claim 8, characterized in that: The preparation method of the battery body comprises: Providing an N-type single crystal silicon substrate; Depositing an intrinsic hydrogenated amorphous silicon film layer, a p-type amorphous silicon layer and a transparent conductive oxide layer in sequence on the first surface of the N-type single crystal silicon substrate; Depositing an intrinsic hydrogenated amorphous silicon film layer, an n-type amorphous silicon layer and a transparent conductive oxide layer in sequence on the second surface of the N-type single crystal silicon substrate to obtain the battery body; wherein the first surface is opposite to the second surface; The target material of the transparent conductive oxide layer includes any one of indium tin oxide, indium oxide doped with tungsten and indium oxide doped with cerium.

13. A solar cell module, characterized in that: The solar cell module comprises several solar cells according to any one of claims 1-7.